Pengaruh Media Tanam Dan Konsentrasi Larutan AB Mix Terhadap Pertumbuhan Dan Hasil Tanaman Kale - Adiwijaya, Hamdan Drian; Lusiana; Nurul F, Dea (OrchidAgro, 2024)
This study aims to determine the effect of the type of growing media and the concentration of the mixed AB solution on the growth and yield of kale using an axis hydroponic system. The research method used was an experimental method with type of planting media included: husk charcoal (M1), rockwool (M2), cocopeat (M3) and the concentration of AB Mix nutrients consisting of: 1750 ppm (N1 ), 2000 ppm (N2), and 2250 ppm (N3). Parameters observed in the study included: plant height, plant diameter, number of leaves, rot length, wet weight per plant, wet weight per plot and leaf area. The results showed that there was an effect of independent treatment of the type of planting media which had a significant effect on plant height, stem diameter, number of leaves, and fresh weight per plot. The concentration of the AB Mix nutrient solution had no significant effect on each treatment. Rockwool (M2) and husk charcoal (M1) planting media produced the best fresh weight with respective weights of 636.33 and 618.67, while the lowest fresh weight was produced by cocopeat growing media, namely 453.56. Keywords: Growing media, Concentration AB Mi,; Hydroponic